The new role of life insurers in Singapore - Chong, Yuan Yuan (2014)
The liberalisation of the Central Provident Fund and the changing environment have brought about a great impact to the role of life insurer. The traditional role of the life insurer is to provide financial security especially, in the event of premature death. Today, the role of the life insurer has expanded Besides providing financial security, it also caters to the health provision, investment and retirement needs of the public. Hence, we see the introduction of health insurance, investment-linked products and annuity insurance.